Bio-based biodegradable adhesive tape based on modified cellulose and preparation method of bio-based biodegradable adhesive tape
By combining modified cellulose and specific additives, combined with 3D printing technology, the problems of insufficient adhesion and durability of tape in the prior art are solved, strong adhesion performance and controllable breaking function are achieved, and the tape is improved Durability and production flexibility solve the problems of limited manufacturing of complex structures and material selection, reduce costs and open up broader application prospects.
Patent Information
- Application Number
- CN202411486936.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-31
AI Technical Summary
The existing technology cannot achieve strong adhesion performance, extend service life, improve appearance, controllable breaking and bonding functions, and customized design, resulting in insufficient adhesion, insufficient strength and durability, poor processing performance, and insufficient production flexibility. , difficulty in manufacturing complex structures, limited material selection, and problems such as long development cycle, unexpected fractures, structural instability and high costs.
Using modified cellulose-based biodegradable tape, including substrate layer, adhesive layer, anti-adhesion layer, surface coating and special functional layers, through the preparation of modified cellulose and the addition of specific adhesives and tackifiers , anti-slip agents, etc., combined with 3D printing technology to prepare tapes, achieve strong adhesion performance and controllable breaking function, and improve the durability and production flexibility of tapes through specific hierarchical structures and materials combinations.
It realizes strong adhesion performance, extends service life, improves appearance, controllable breaking and bonding functions, improves the durability and production flexibility of the tape, reduces costs, enhances market competitiveness, and expands wider applications prospect.
Smart Images

Figure CN119220187A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging materials, in particular to a bio-based biodegradable adhesive tape based on modified cellulose and a preparation method thereof. Background Art
[0002] Modified cellulose is a renewable, biodegradable material with good mechanical properties and plasticity. By modifying and modulating cellulose materials, its properties can be improved to make it suitable for tape preparation. At the same time, improving preparation methods and introducing new technologies provide more possibilities for the preparation of bio-based tapes.
[0003] At present, the global demand for environmental protection and sustainable development is increasing. The extensive use of traditional petrochemical-based tapes has caused serious environmental problems. They are difficult to degrade and pose a threat to biodiversity. Long-term smelling of tapes or contact with chemicals on them has adverse effects on human health, especially tapes with oil-based glues. The diluents are mainly volatile hazardous chemicals such as toluene, which can damage liver function once inhaled. After long-term use, the viscosity of the tape may decrease and age, resulting in a decrease in the adhesive effect. In addition, the cleanliness of the surface of the object is required to be high. If there are impurities such as dust and oil on the surface, it will affect the adhesive effect.
[0004] Therefore, it is very necessary to propose a bio-based biodegradable tape based on modified cellulose and a preparation method thereof in the present application to solve the problems in the background.
[0005] 1. Patent document CN111621239B discloses a fully biodegradable tape and a method for preparing the same. The above patent achieves complete biodegradability, and the main components are all biodegradable. The final degradation products are carbon dioxide, water and small molecule biomass, which are harmless to the environment. Organic or inorganic fillers are added to reduce production costs. The tape can be prepared through existing mature equipment and processes, and the product has good adaptability. However, the above patent cannot achieve strong adhesion performance.
[0006] 2. Patent document CN109679519B discloses a plant-based degradable tape and its preparation method. The above patent makes the tape degradable through the selection of tape raw materials and the preparation process, which greatly reduces the pollution to the environment caused by the large-scale use of tape. Furthermore, when recycling cartons using tape, the step of removing the tape can be reduced to reduce the recycling cost of carton recycling, improve the recycling rate of cartons, and reduce the consumption of natural resources. However, the above patent cannot extend the service life and improve the appearance.
[0007] 3. Patent document CN109679518B discloses a plant-based easy-tear tape and its preparation method. The above patent achieves that the tape is easier to tear than BOPP tape through the selection of tape raw materials and the preparation process, and has higher tensile strength than traditional paper-based tape, which greatly improves its convenience in the field of cultural products. Furthermore, the plant-based easy-tear tape prepared by the present invention is biodegradable and environmentally friendly, which conforms to the trend of society's emphasis on environmental protection requirements, but the above patent cannot achieve the controllable breaking and bonding functions of the tape during use.
[0008] 4. Patent document CN114806431B discloses a flame retardant and degradable tape and a preparation method thereof. The above patent realizes that the flame retardant and degradable tape has high adhesion and excellent flame retardant properties. The raw materials come from discarded PBT plastic and are biodegradable. It has broad market application prospects. However, the above patent cannot achieve customized design, complex structure manufacturing, material diversity and rapid prototyping.
[0009] In summary, the above patents cannot achieve the functions of strong adhesion performance, extended service life and improved appearance, controllable breaking and bonding of the tape during use, and customized design, resulting in insufficient adhesion, insufficient strength and durability, poor processing performance, insufficient production flexibility, difficulty in manufacturing complex structures, limited material selection, long development cycle, unexpected breakage, unstable structure, and high cost;
[0010] To this end, the present application proposes a bio-based biodegradable tape based on modified cellulose and a preparation method thereof that can achieve the functions of strong adhesion performance, extended service life and improved appearance, controllable breaking and bonding functions during use of the tape, and customized design functions. Summary of the invention
[0011] The object of the present invention is to provide a bio-based biodegradable tape based on modified cellulose and a preparation method thereof, so as to solve the technical problems proposed in the above-mentioned background technology, namely, the inability to achieve the functions of strong adhesion performance, extended service life and improved appearance, controllable breaking and bonding functions of the tape during use, and customized design functions, resulting in insufficient adhesion, insufficient strength and durability, poor processing performance, insufficient production flexibility, difficulty in manufacturing complex structures, limited material selection, long development cycle, accidental breakage, unstable structure, and high cost.
[0012] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a bio-based biodegradable tape based on modified cellulose, comprising a substrate layer, an adhesive layer, an anti-adhesive layer, a surface coating and a special functional layer, wherein the substrate layer is a tape body composed of 60%-70% modified cellulose and 0.1%-0.3% hardener, and the modified cellulose comprises the following raw materials in weight percentage: 21%-25% carboxymethyl cellulose ester, 18%-20% nitrocellulose, 20%-22% cellulose acetate, and 1%-3% hydroxypropyl cellulose;
[0013] The thickness of the substrate layer is 60 microns.
[0014] Preferably, the adhesive layer is composed of an adhesive, a tackifier, a softener, a filler, a stabilizer and a cross-linking agent;
[0015] The adhesive is 35% acrylate copolymer, the tackifier is 10% polycaprolactone and 5% polylactic acid, the softener is a starch-based softener and 4% castor oil, the starch-based softener is 3% acetic starch and 5% oxidized starch, and the filler is 1% talc and 2% calcium carbonate;
[0016] The stabilizer is an antioxidant and an ultraviolet absorber, the antioxidant is 2% tea polyphenols and 1.5% phytic acid, and the ultraviolet absorber is benzophenone and benzotriazole;
[0017] The cross-linking agent is a natural cross-linking agent, which adopts guar root extract, and the guar root extract is 6% guar cross-linking polymer.
[0018] Preferably, the anti-sticking layer uses 30% bio-silicone oil, a surfactant and 8% silicon dioxide nanoparticles, the diameter of the silicon dioxide nanoparticles is 45 nanometers, and the surfactant is 10% fatty acid ester polyoxyethylene ester.
[0019] Preferably, the surface coating is made of 55% acrylic resin, 15% polydimethylsiloxane, 8% plasticizer, and 13% solvent, the plasticizer is dioctyl phthalate, and the solvent is isopropyl alcohol.
[0020] Preferably, the special functional layer uses a waterproof film, a conductive filler, and an antibacterial agent, the antibacterial agent is 1.8% benzalkonium bromide, the waterproof film uses 4% silane coupling agent and 2% polysiloxane, and the conductive filler uses 0.5% carbon black, 0.2% graphene and 1% conductive polymer.
[0021] Preferably, the substrate layer is a tape support structure located at the bottom of the entire tape, the adhesive layer is close to the left side of the substrate layer, the anti-adhesive layer is located on the surface of the tape, the anti-adhesive layer is above the adhesive layer, the surface coating is located between the adhesive layer and the anti-adhesive layer, and the special functional layer is located above the adhesive layer;
[0022] The thickness of the adhesive layer is 0.04 mm, the thickness of the anti-sticking layer is 0.01 mm, the thickness of the surface coating is 6 microns, and the thickness of the special functional layer is 5 microns.
[0023] Preferably, the bio-based biodegradable tape based on modified cellulose further comprises the following raw materials in weight percentage: 0.7% anti-slip agent, 0.3% waterproof agent, 1.1% degradable connector, 0.8% mycelium fibroin;
[0024] The degradable connector is polyhydroxyalkanoate, the waterproof agent uses chitosan and polyurethane in a ratio of 3:2, and the anti-slip agent is a bio-based resin.
[0025] Preferably, the waterproof film is coated with two layers of nanofiber membranes, the carbon black diameter is 0.3 nanometers, and the BET specific surface area of the carbon black is 30-160m 2 / g.
[0026] Preferably, the preparation method comprises the following steps:
[0027] (1) adding the modified cellulose and the hardener into a high-speed mixer and stirring at high speed for 30-45 minutes, then adding the adhesive, the tackifier, the softener, the stabilizer and the natural cross-linking agent into the high-speed mixer and stirring for 10-15 minutes to mix evenly;
[0028] (2) adding the mixture obtained in (1) into a centrifuge tube to separate impurities and undissolved solid cellulose particles in the cellulose solution, adding bio-silicone oil, surfactant, acrylic resin, polydimethylsiloxane, and passing the solution through a solution storage tank, a spinning head, and a collector to form a continuous fiber flow, adding a plasticizer, an antibacterial agent, a silane coupling agent, polysiloxane, a conductive filler, a solvent, and silica nanoparticles during the fiber flow generation process, drying and curing in a vacuum dryer at 60-80° C., and finally cooling and winding to produce a bio-based adhesive;
[0029] (3) The bio-based adhesive obtained in (2) is three-dimensionally formed by a 3D printer to prepare a bio-based biodegradable adhesive tape semi-finished product with an adhesive thickness of 15 μm;
[0030] (4) Cutting and rolling the semi-finished product obtained in (3), performing surface treatment with a plasma instrument, obtaining an adhesive tape and performing vacuum packaging.
[0031] Preferably, the method of use further comprises the following steps:
[0032] (5) Preparation of modified cellulose (introducing high molecular weight side chains from the side through active chain segments on the macromolecular chains of the fiber)
[0033] Carboxymethyl cellulose ester: wood pulp is crushed, alkali-leached, acid-leached, bleached, impurities and pigments are removed, and refined cotton is obtained. The refined cotton reacts with chloroacetic acid and sodium hydroxide. After the etherification reaction is completed, the product is washed and dehydrated to remove excess sodium chloride and water. The wet sodium carboxymethyl cellulose is dried by air flow to remove water from the wet sodium carboxymethyl cellulose to obtain dry sodium carboxymethyl cellulose. The dried sodium carboxymethyl cellulose is sieved and ground;
[0034] Nitrocellulose: After loosening and drying, the chemical cotton is esterified with a mixed acid of nitric acid and sulfuric acid to esterify the -OH group in the cellulose into -ONO2. After the esterification reaction, the product is washed, neutralized and dried;
[0035] Cellulose acetate: Add 5g of absorbent cotton, 35ml of glacial acetic acid, 4 drops of concentrated sulfuric acid and 25ml of acetic anhydride to a flask, cover with a watch glass, heat in a 50℃ water bath, and stir to acylate the cellulose for about 1.5-2h until a homogeneous paste is formed, heat to 60℃, add 12.5ml of 80% acetic acid, keep warm at 60℃ for 15min, add 12ml of water with stirring, and then add 100ml of water with rapid stirring to precipitate white, loose cellulose acetate, transfer the precipitated cellulose acetate to a Buchner funnel, filter by suction, disperse in water, pour off the upper liquid, wash until neutral, and dry at 105℃;
[0036] Hydroxypropyl cellulose: The cellulose is crushed and screened to remove impurities and particles that do not meet the requirements. The cellulose is pre-treated with alkalization using sodium hydroxide solution to fully swell and expose more hydroxyl groups for reaction with propylene oxide. The pre-treated cellulose is mixed with propylene oxide in a ratio of 4:3 and etherification reaction is carried out at 80°C for 1.5h. The hydroxyl groups in the cellulose molecules undergo substitution reaction with the epoxy groups of propylene oxide. The reaction product is washed and filtered to remove impurities such as unreacted propylene oxide and sodium hydroxide, and finally dried.
[0037] (6) Preparation of polyhydroxyalkanoates
[0038] Cultivating Alcaligenes, inoculating the strain into a fermentation medium containing a carbon source, a nitrogen source and other necessary nutrients, allowing the microorganism to utilize the carbon source to synthesize polyhydroxyalkanoates, and after the fermentation is completed, obtaining a bacterial cell precipitate containing polyhydroxyalkanoates by solid-liquid separation, breaking the bacterial cell wall to release the polyhydroxyalkanoates, and further purifying the polyhydroxyalkanoates by plate and frame filtration and centrifugal separation;
[0039] (7) Preparation of acrylic acid ester copolymer
[0040] Acrylate monomers and peroxides are used as free radical initiators for polymerization, and monomer molecules form polymer chains through free radical addition reactions. After the polymerization reaction, the product is washed, dried, and purified to remove unreacted monomers, initiator residues, and other impurities.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The present invention achieves strong adhesion performance by formulating modified cellulose, solves the problems of insufficient adhesion, insufficient strength and durability, and poor processing performance, enhances the adhesion of the tape, enables it to achieve better adhesion on the surfaces of different objects, and is easier to shape and cut during the production process;
[0043] 2. The present invention achieves the function of extending the service life and improving the appearance by adding edge adhesive, solves the problem that the edge part is easy to fall off, increases the strength of the edge of the tape, and prevents debonding;
[0044] 3. The present invention realizes the functions of customized design, complex structure manufacturing, material diversity and rapid prototyping through 3D printing, which solves the problems of insufficient production flexibility, difficulty in complex structure manufacturing, limited material selection, long development cycle and high cost, improves market competitiveness and opens up broader application prospects in the field of tape manufacturing;
[0045] 4. The present invention introduces special breaking links into the tape structure to achieve controllable breaking and bonding functions of the tape during use, solves the problems of accidental breakage, unstable structure and high cost, improves the recycling rate and environmental protection of the tape, and facilitates decomposition and recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a schematic diagram of the process of preparing the adhesive tape of the present invention;
[0047] Figure 2 This is a schematic diagram of a partial process for preparing modified cellulose according to the present invention;
[0048] Figure 3 This is a schematic diagram of a partial process for preparing modified cellulose according to the present invention;
[0049] Figure 4 This is a schematic diagram of the process for preparing polyhydroxyalkanoate of the present invention;
[0050] Figure 5 This is a schematic diagram of the process for preparing an acrylic ester copolymer according to the present invention;
[0051] Figure 6 This is a schematic diagram of the process for preparing fatty acid ester polyoxyethylene ester of the present invention;
[0052] Figure 7 This is a biodegradability test diagram of the present invention. DETAILED DESCRIPTION
[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] See also Figure 2 and Figure 3 , an embodiment provided by the present invention: a bio-based biodegradable adhesive tape based on modified cellulose and a preparation method thereof, comprising a substrate layer, an adhesive layer, an anti-adhesive layer, a surface coating and a special functional layer, wherein the substrate layer is a tape body composed of 60% modified cellulose and 0.1% hardener, the modified cellulose comprises the following raw materials in weight percentage: 21% carboxymethyl cellulose ester, 18% nitrocellulose, 20% cellulose acetate, 1% hydroxypropyl cellulose, and the thickness of the substrate layer is 60 microns;
[0055] Further, modified cellulose is prepared:
[0056] Carboxymethyl cellulose ester: wood pulp is crushed, alkali-leached, acid-leached, bleached, impurities and pigments are removed, and refined cotton is obtained. The refined cotton reacts with chloroacetic acid and sodium hydroxide. After the etherification reaction is completed, the product is washed and dehydrated to remove excess sodium chloride and water. The wet sodium carboxymethyl cellulose is dried by air flow to remove water from the wet sodium carboxymethyl cellulose to obtain dry sodium carboxymethyl cellulose. The dried sodium carboxymethyl cellulose is sieved and ground;
[0057] Nitrocellulose: After loosening and drying, the chemical cotton is esterified with a mixed acid of nitric acid and sulfuric acid to esterify the -OH group in the cellulose into -ONO2. After the esterification reaction, the product is washed, neutralized and dried;
[0058] Cellulose acetate: Add 5g of absorbent cotton, 35ml of glacial acetic acid, 4 drops of concentrated sulfuric acid and 25ml of acetic anhydride to a flask, cover with a watch glass, heat in a 50℃ water bath, and stir to acylate the cellulose for about 1.5-2h until a homogeneous paste is formed, heat to 60℃, add 12.5ml of 80% acetic acid, keep warm at 60℃ for 15min, add 12ml of water with stirring, and then add 100ml of water with rapid stirring to precipitate white, loose cellulose acetate, transfer the precipitated cellulose acetate to a Buchner funnel, filter by suction, disperse in water, pour off the upper liquid, wash until neutral, and dry at 105℃;
[0059] Hydroxypropyl cellulose: The cellulose is crushed and screened to remove impurities and particles that do not meet the requirements. The cellulose is pre-treated with alkalization using sodium hydroxide solution to allow it to fully swell and expose more hydroxyl groups to react with propylene oxide. The pre-treated cellulose is mixed with propylene oxide in a ratio of 4:3 and an etherification reaction is carried out at 80°C for 1.5 hours. The hydroxyl groups in the cellulose molecules undergo a substitution reaction with the epoxy groups of propylene oxide. The reaction products are washed and filtered to remove unreacted impurities such as propylene oxide and sodium hydroxide, and finally dried.
[0060] See also Figure 5 , an embodiment provided by the present invention: a bio-based biodegradable adhesive tape based on modified cellulose and a preparation method thereof, wherein the adhesive layer is composed of an adhesive, a tackifier, a softener, a filler, a stabilizer and a cross-linking agent;
[0061] The adhesive is 35% acrylate copolymer, the tackifier is 10% polycaprolactone and 5% polylactic acid, the softener is 3% acetic starch, 5% oxidized starch and 4% castor oil, the filler is 1% talc and 2% calcium carbonate, the stabilizer is 2% tea polyphenols, 1.5% phytic acid, benzophenone and benzotriazole, and the crosslinker is 6% guar-linked polymer;
[0062] Furthermore, first, methyl methacrylate, an acrylic acid ester monomer, and benzoyl oxide are selected as free radical initiators for polymerization reaction, and monomer molecules form polymer chains through free radical addition reaction. Then, after the polymerization reaction is completed, the product is washed, dried, and purified to remove unreacted monomers, initiator residues and other impurities.
[0063] See also Figure 6 , an embodiment provided by the present invention: a bio-based biodegradable tape based on modified cellulose and a preparation method thereof, wherein the surface coating adopts 55% acrylic resin, 15% polydimethylsiloxane, 8% plasticizer dioctyl phthalate, and 13% solvent isopropyl alcohol;
[0064] The special functional layer uses a waterproof film, a conductive filler, and an antibacterial agent. The antibacterial agent is 1.8% benzalkonium bromide, the waterproof film uses 4% silane coupling agent and 2% polysiloxane, and the conductive filler uses 0.5% carbon black, 0.2% graphene, and 1% conductive polymer.
[0065] The anti-sticking layer uses 30% bio-silicone oil, 10% fatty acid ester polyoxyethylene ester and 8% silicon dioxide nanoparticles, and the diameter of the silicon dioxide nanoparticles is 45 nanometers;
[0066] Furthermore, first, a catalyst quaternary ammonium compound is added to the reaction system and properly activated to ensure its catalytic activity. Then, under the action of the catalyst, fatty acids are extracted from animal and plant oils and fats and reacted with ethylene oxide to react. The ethylene oxide molecules are added one by one to the carboxyl groups of the fatty acids to form polyoxyethylene chains. Finally, after the reaction is completed, the product is separated from the reaction mixture by distillation and extraction, and impurities and unreacted raw materials are removed to obtain fatty acid ester polyoxyethylene ester.
[0067] See also Figure 4 , an embodiment provided by the present invention: a bio-based biodegradable tape based on modified cellulose and a preparation method thereof, further comprising the following raw materials in weight percentage: 0.7% anti-slip agent, 0.3% waterproof agent, 1.1% degradable connector, 0.8% mycelium fibroin;
[0068] The degradable linker is polyhydroxyalkanoate, the waterproofing agent uses chitosan and polyurethane in a ratio of 3:2, and the anti-slip agent is a bio-based resin;
[0069] Furthermore, first, Alcaligenes is cultured and the strain is inoculated into a fermentation medium containing a carbon source, a nitrogen source and other necessary nutrients, so that the microorganism utilizes the carbon source to synthesize polyhydroxyalkanoates. Then, after the fermentation is completed, a bacterial precipitate containing polyhydroxyalkanoates is obtained by solid-liquid separation. Finally, the bacterial cell wall is broken to release the polyhydroxyalkanoates, and the polyhydroxyalkanoates are further purified by plate and frame filtration and centrifugal separation.
[0070] See also Figure 1 , the present invention provides an embodiment: a bio-based biodegradable tape based on modified cellulose and a preparation method thereof, wherein the substrate layer is a tape support structure located at the bottom of the entire tape, the adhesive layer is closely attached to the left side of the substrate layer, the anti-adhesive layer is located on the surface of the tape, the anti-adhesive layer is above the adhesive layer, the surface coating is located between the adhesive layer and the anti-adhesive layer, and the special functional layer is located above the adhesive layer;
[0071] The thickness of the adhesive layer is 0.04 mm, the thickness of the anti-adhesive layer is 0.01 mm, the thickness of the surface coating is 6 microns, and the thickness of the special functional layer is 5 microns;
[0072] further,
[0073] (1) adding the modified cellulose and the hardener into a high-speed mixer and stirring at high speed for 30-45 minutes, then adding the adhesive, the tackifier, the softener, the stabilizer and the natural cross-linking agent into the high-speed mixer and stirring for 10-15 minutes to mix evenly;
[0074] (2) adding the mixture obtained in (1) into a centrifuge tube to separate impurities and undissolved solid cellulose particles in the cellulose solution, adding bio-silicone oil, surfactant, acrylic resin, polydimethylsiloxane, and passing the solution through a solution storage tank, a spinning head, and a collector to form a continuous fiber flow, adding a plasticizer, an antibacterial agent, a silane coupling agent, polysiloxane, a conductive filler, a solvent, and silica nanoparticles during the fiber flow generation process, drying and curing in a vacuum dryer at 60-80° C., and finally cooling and winding to produce a bio-based adhesive;
[0075] (3) The bio-based adhesive obtained in (2) is three-dimensionally formed by a 3D printer to prepare a bio-based biodegradable adhesive tape semi-finished product with an adhesive thickness of 15 μm;
[0076] (4) Cutting and rolling the semi-finished product obtained in (3), performing surface treatment with a plasma instrument, obtaining an adhesive tape, and conducting a biodegradability test such as Figure 7 .
[0077] Biodegradability testing was performed according to ASTM D6400 under aerobic composting conditions.
[0078] Working principle: cellulose is selected as the base material. Cellulose is a natural polymer compound derived from plant cell walls, which is renewable and biodegradable. The cellulose is modified; the modified cellulose is mixed with other additives in a certain proportion to form the basic material of the tape; the basic material is processed into a tape with a specific thickness, width and length through a specific processing technology (spinning, coating, 3D printing); during the processing, the tape also needs to be surface treated to improve its adhesion or weather resistance and other properties;
[0079] Modified cellulose-based tape forms a strong adhesion with the substrate through the adhesive layer on its surface; when the tape is discarded, in the natural environment, microorganisms will attach to the surface of the tape and secrete biological enzymes such as cellulase. These enzymes can act on the modified cellulose molecular chain, causing it to break and degrade, and eventually decompose into harmless substances such as carbon dioxide and water.
[0080] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A bio-based biodegradable adhesive tape based on modified cellulose, characterized in that: It includes a substrate layer, an adhesive layer, an anti-adhesive layer, a surface coating layer and a special functional layer. The substrate layer is a tape body composed of 60%-70% modified cellulose and 0.1%-0.3% hardener. The modified cellulose includes the following raw materials in weight percentage: 21%-25% carboxymethyl cellulose ester, 18%-20% nitrocellulose, 20%-22% cellulose acetate, and 1%-3% hydroxypropyl cellulose. The thickness of the substrate layer is 60 microns.
2. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 1, characterized in that: The adhesive layer is composed of an adhesive, a tackifier, a softener, a filler, a stabilizer and a cross-linking agent; The adhesive is 35% acrylate copolymer, the tackifier is 10% polycaprolactone and 5% polylactic acid, the softener is a starch-based softener and 4% castor oil, the starch-based softener is 3% acetic starch and 5% oxidized starch, and the filler is 1% talc and 2% calcium carbonate; The stabilizer is an antioxidant and a UV absorber, the antioxidant is 2% tea polyphenols and 1.5% phytic acid, and the UV absorber is benzophenone and benzotriazole; The cross-linking agent is a natural cross-linking agent, and the natural cross-linking agent adopts guar root extract, and the guar root extract is 6% guar cross-linking agent.
3. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 1, characterized in that: The anti-sticking layer is made of 30% bio-silicone oil, a surfactant and 8% silicon dioxide nanoparticles, the diameter of the silicon dioxide nanoparticles is 45 nanometers, and the surfactant is 10% fatty acid ester polyoxyethylene ester.
4. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 1, characterized in that: The surface coating is made of 55% acrylic resin, 15% polydimethylsiloxane, 8% plasticizer, and 13% solvent, the plasticizer is dioctyl phthalate, and the solvent is isopropyl alcohol.
5. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 1, characterized in that: The special functional layer adopts a waterproof film, a conductive filler, and an antibacterial agent. The antibacterial agent is 1.8% benzalkonium bromide, the waterproof film adopts 4% silane coupling agent and 2% polysiloxane, and the conductive filler adopts 0.5% carbon black, 0.2% graphene and 1% conductive polymer.
6. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 1, characterized in that: The substrate layer is the tape support structure located at the bottom of the tape as a whole, the adhesive layer is close to the left side of the substrate layer, the anti-adhesive layer is located on the surface of the tape, the anti-adhesive layer is above the adhesive layer, the surface coating is located between the adhesive layer and the anti-adhesive layer, and the special functional layer is located above the adhesive layer; The thickness of the adhesive layer is 0.04 mm, the thickness of the anti-sticking layer is 0.01 mm, the thickness of the surface coating is 6 microns, and the thickness of the special functional layer is 5 microns.
7. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 1, characterized in that: The modified cellulose-based biodegradable adhesive tape further comprises the following raw materials in weight percentage: 0.7% anti-slip agent, 0.3% waterproof agent, 1.1% degradable connector, and 0.8% mycelium fibroin; The degradable connector is polyhydroxyalkanoate, the waterproof agent uses chitosan and polyurethane in a ratio of 3:2, and the anti-slip agent is a bio-based resin.
8. The bio-based biodegradable adhesive tape based on modified cellulose according to claim 5, characterized in that: The waterproof film is coated with two layers of nanofiber membranes, the carbon black diameter is 0.3 nanometers, and the BET specific surface area of the carbon black is 30-160 m2 / g.
9. A method for preparing a bio-based biodegradable adhesive tape based on modified cellulose, applicable to the bio-based biodegradable adhesive tape based on modified cellulose according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) Add modified cellulose and hardener into a high-speed mixer and stir at high speed for 30-45 minutes, then add adhesive, tackifier, softener, stabilizer and natural cross-linking agent into the high-speed mixer and continue stirring for 10-15 minutes to mix evenly; (2) adding the mixture obtained in (1) into a centrifuge tube to separate impurities and undissolved solid cellulose particles in the cellulose solution, adding bio-silicone oil, surfactant, acrylic resin, polydimethylsiloxane, and passing the solution through a solution storage tank, a spinning head, and a collector to form a continuous fiber flow, adding a plasticizer, an antibacterial agent, a silane coupling agent, polysiloxane, a conductive filler, a solvent, and silica nanoparticles during the fiber flow generation process, drying and curing in a vacuum dryer at 60-80°C, and finally cooling and winding to produce a bio-based adhesive; (3) The bio-based adhesive obtained in (2) is three-dimensionally formed by a 3D printer to prepare a bio-based biodegradable adhesive tape semi-finished product with an adhesive thickness of 15 μm; (4) The semi-finished product obtained in (3) is cut and rolled, and surface treated by a plasma instrument to obtain an adhesive tape and vacuum package it.
10. The method for preparing a bio-based biodegradable adhesive tape based on modified cellulose according to claim 9, characterized in that: The method of use also includes the following steps: (5) Preparation of modified cellulose, by introducing high molecular weight side chains from the side through active chain links on the macromolecular chains of the fibers; Carboxymethyl cellulose ester: wood pulp is crushed, alkali-leached, acid-leached, bleached, impurities and pigments are removed, and refined cotton is obtained. The refined cotton reacts with chloroacetic acid and sodium hydroxide. After the etherification reaction is completed, the product is washed and dehydrated to remove excess sodium chloride and water. The wet sodium carboxymethyl cellulose is dried by air flow to remove water from the wet sodium carboxymethyl cellulose to obtain dry sodium carboxymethyl cellulose. The dried sodium carboxymethyl cellulose is sieved and ground; Nitrocellulose: After loosening and drying, the chemical cotton is esterified with a mixed acid of nitric acid and sulfuric acid to esterify the -OH group in the cellulose into -ONO2. After the esterification reaction, the product is washed, neutralized and dried; Cellulose acetate: Add 5g of absorbent cotton, 35ml of glacial acetic acid, 4 drops of concentrated sulfuric acid and 25ml of acetic anhydride to a flask, cover with a watch glass, heat in a 50℃ water bath, and stir to acylate the cellulose for about 1.5-2h until a homogeneous paste is formed, heat to 60℃, add 12.5ml of 80% acetic acid, keep warm at 60℃ for 15min, add 12ml of water with stirring, and then add 100ml of water with rapid stirring to precipitate white, loose cellulose acetate, transfer the precipitated cellulose acetate to a Buchner funnel, filter by suction, disperse in water, pour off the upper liquid, wash until neutral, and dry at 105℃; Hydroxypropyl cellulose: The cellulose is crushed and screened to remove impurities and particles that do not meet the requirements. The cellulose is pre-treated with alkalization using sodium hydroxide solution to fully swell and expose more hydroxyl groups for reaction with propylene oxide. The pre-treated cellulose is mixed with propylene oxide in a ratio of 4:3 and etherification reaction is carried out at 80°C for 1.5h. The hydroxyl groups in the cellulose molecules undergo substitution reaction with the epoxy groups of propylene oxide. The reaction product is washed and filtered to remove impurities such as unreacted propylene oxide and sodium hydroxide, and finally dried. (6) Preparation of polyhydroxyalkanoates Cultivating Alcaligenes, inoculating the strain into a fermentation medium containing a carbon source, a nitrogen source and other necessary nutrients, allowing the microorganism to utilize the carbon source to synthesize polyhydroxyalkanoates, and after the fermentation is completed, obtaining a bacterial cell precipitate containing polyhydroxyalkanoates by solid-liquid separation, breaking the bacterial cell wall to release the polyhydroxyalkanoates, and further purifying the polyhydroxyalkanoates by plate and frame filtration and centrifugal separation; (7) Preparation of acrylic acid ester copolymer Acrylate monomers and peroxides are used as free radical initiators for polymerization, and monomer molecules form polymer chains through free radical addition reactions. After the polymerization reaction, the product is washed, dried, and purified to remove unreacted monomers, initiator residues, and other impurities.